Techno-Economic Analysis of Dme Implementation in Indonesia’s Household Energy Sector - Faqih Supriyadi; Irawan Adhi Putra; Riva Yudha Abriyant; Danang Sismartono; Cahyo Setyo Wibowo; Bambang Priyono (Scientific Contributions Oil and Gas, 2025)
Indonesia's increasing demand for Liquefied Petroleum Gas (LPG) – projected to reach 13.2 million tonnes by 2050 – and its heavy dependence on imports, require alternative and sustainable fuel solutions. Among the options under development, researchers and industry stakeholders consider Dimethyl Ether (DME)—particularly from abundant domestic low-rank coal—a viable and strategic substitute. DME has physicochemical properties similar to LPG, as well as its compatibility with existing storage and distribution infrastructure. This comprehensive study evaluates the techno-economic aspects of replacing LPG with coal-based DME in the household sector. The factors analyzed include energy equity, production and distribution costs, and projected fiscal impacts on the national economy. Assuming a production capacity of 1.4 million tons per year and an Internal Rate of Return (IRR) of 12%, analysts estimate DME’s Free-On-Board (FOB) price at IDR 8.03 million per ton, with a benchmark price equivalent to LPG at IDR 16,666/kg. At this rate, replacing imported LPG with domestic DME can save the country's foreign exchange around IDR10.71 trillion per year, but has the potential to increase subsidies by IDR3.97 trillion. The government can use the foreign exchange savings to cover the potential increase in DME subsidies.